HUMANISTICS LANGUAGE TEACHING, FACILITATION, AND CLASSROOM CONVERSATION - Clifton Jonathan (Universitas Katolik Indonesia Atma Jaya, 2006)
Despite the fact that teachers of foreign languages often talk about ‘conversation classes’, the provision of conversation and instruction is often considered to be mutually exclusive (Seedhouse 1996). However, this paper proposes that humanistic language teaching (HLT) is one way of resolving this paradox. A language instructor has two sources of authority: institutional and linguistic. A facilitator, using humanistic teaching techniques, gives up institutional authority and so ‘frees up’ the classroom turn-taking system so that the strict initiation-response-feedback (IRF) pattern of most teaching is transformed into a conversational pattern where any participant is potentially a next speaker. Consequently, a conversation can take place in a class. On the other hand, linguistic authority is still exercised in the form of side-sequences which allow the facilitator to provide minimally invasive feedback without affecting the overall orientation to conversational rules of turn-taking. Keywords: facilitation, humanistic language teaching, identity, conversation, initiation-response-feedback